Discovery Learning Model To Improve The Learning Achievement Of Class 1 Students - Melatisari, Agatha Andaning (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Student learning outcomes are influenced by the learning model chosen by the teacher in learning. The teacher is the dominant factor in the learning process so that it is a factor that influences the process and learning outcomes. Media, methods, and learning models carried out by teachers are liked or liked by students, so student learning interest will increase. So that students will easily master the subject matter. The problem discussed in this study is how to improve learning outcomes through the Discover Learning model. Learning Discovery Learning is more complex, requires a lot of thinking activities and not infrequently even requires a number of physical activities. Discovery Learning Learning Model is a learning model where students understand their own concepts, meanings, and relationships through an intuitive process. The purpose of this research is to improve the learning outcomes of grade I students. In this study the authors want to improve the condition of students so that students' activeness using the Discovery Learning model can be better, so that learning completeness will be more successful. So far, in teaching and learning activities, teachers still use old methods such as lectures, this method will make students passive or not. Conclusions using the Discovery Learning learning model can improve student learning outcomes in class I.